Pengaruh Kompensasi dan Work-Life Balance Terhadap Retensi Tenaga Medis di Rumah Sakit Pirngadi Medan: Penelitian - Nesi Suntiarli Togatorop; Rindu Siburian; Rahel Octavia Sinaga; Ronael Sihotang; Yohanes Waruwu; Anna Laura Situmeang; Tantri Lolita Sipayung (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study aims to evaluate the impact of compensation and work-life balance on retaining medical personnel at Dr. Pirngadi Regional General Hospital, Medan. This study employed a quantitative approach through a survey method. The population consisted of all 435 medical personnel at Dr. Pirngadi Regional General Hospital, with a sample size of 209 respondents determined using the Slovin formula. Data were obtained through questionnaires and analyzed using multiple linear regression using SPSS version 26 software. The study's findings indicate that compensation and work-life balance have a positive and significant impact on medical personnel retention, both separately and together. Work-life balance is the most influential variable on medical personnel retention. The coefficient of determination indicates that compensation and work-life balance explain 36% of the variation in medical personnel retention, while the remaining 64% is influenced by other variables outside this study. This study emphasizes that fair compensation management and the implementation of sound work-life balance policies are crucial for improving healthcare personnel retention.